Perilaku Keagamaan Hindu pada Generasi Alpha sebagai Agama Minoritas di Desa Pengalangan Menganti Gresik - Mufarochah, Siti; Agustin, Nurul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
Religion is a basic guideline in behavior so that the good or bad behavior of a person can be seen from the religious perseverance possessed by a person, especially for the alpha generation who were born in the era of technological development and everything is instant. Hinduism in Pengalangan village is small in number so that this makes the religious behavior they have different from Hinduism in other areas. The purpose of this study is to see and examine the religious behavior of Hindus in Pengalangan village, Menganti, Gresik, especially in the alpha generation. The method used in this study is a type of descriptive qualitative research with observation, interview and documentation techniques. The results of this study are that the alpha generation who are Hindu can still maintain routine religious behavior even though technology is increasingly advanced and still have a sense of tolerance for the majority religion in the Pengalangan Menganti Gresik area.Keywords: Religious Behavior, Alpha Generation, Minority.